Pandangan Muhammadiyah dan NU Terhadap Kebijakan Pemerintah Orde Baru Mengenai Penyeragaman Hari Raya Idul Fitri - Fatimah, Anis (Al-Isnad: Journal of Islamic Civilization History and Humanities, 2021)
This paper tells about the New Order government policy in carrying out the uniformity of the Eid al-Fitr, thus demanding that several Islamic organization groups such as Muhammadiyah and NU carry out Eid al-Fitr simultaneously even though the method was always different in determining it. This research uses historical methodology through four main steps of historical method, namely: (1) heuristics, (2) source criticism, (3) interpretation, and (4) historiography. The results of this study indicate that government policies during the New Order era greatly influenced the politics of Islamic mass organizations in determining the time of Eid. This policy resulted in decisions that must be obeyed by all Indonesian people, especially Islamic organizations, so that the determination of the beginning of the qamariah month during the New Order period was almost always uniform.